The Mystical Aspect of Ibn Baṭṭūṭa’s Travels: The Spiritual Visions That Shaped Ibn Baṭṭūṭa’s Path - Al-Khaffaf, Ibrahim (Archaeopress, 2024)
Abū ʿAbd Allāh Muḥammad Ibn ʿAbd Allāh al-Lawātī al-Ṭanjī Ibn Baṭṭūṭa (1304–1377) was born in Tangier, Morocco. Besides being one of the most important travellers historically, he was a Muslim scholar of Islamic law and a judge. His journey started when he was only twenty-one years old: and he travelled through the entire Islamic world of the time. The original full title of Ibn Baṭṭūṭa’s Riḥla (‘Travels’) is: Tuḥfat al-nuẓẓār fī gharāʾib al-amṣār wa-ʿajāʾib al-asfār (‘A Masterpiece to Those Who Contemplate the Wonders of Cities and the Marvels of Travelling’). As the words in the title suggest, the work...